Analisis Kemampuan Daya Serap Mahasiswa Pada Mata Kuliah Geometri Transformasi - Putri, Darvi Mailisa; Amalina, Amalina (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The student's absorption of learning material is one of the factors that can influence the efforts of students to achieve learning outcomes. Absorption can be a benchmark for knowing how far a student understands learning material. Therefore, this study aims to analyze the level of absorptive ability of the UIN Imam Bonjol Padang Tarbiyah Faculty of Mathematics Tadris Study Program at the transformation geometry subject. The study uses statistical estimation, namely the ability of the absorption of students in the transformation geometry subject to the lowest or equal to 75% of the maximum value. The data analysis of the research was carried out manually by using the parametric statistical test formula to find out the truth of the statement or the hypothesis that had been hypothesized. In this study z-test one sample in one direction left side. In addition, hypothesis testing is also carried out using the help of SPSS applications. The results show that and. This means that Ho is accepted. Thus it can be seen that the ability of student absorption in the transformation geometry subject is the lowest or equal to 75% of the maximum value. In other words, the average absorption of students towards transformation geometry courses is more than or equal to 75. So it can be concluded that the absorption of students in the geometry subject of transformation is quite good.Keywords: student absorption, transformation geometry